Antenna bandwidth broadening with a negative impedance converter. Issue 3 (3rd June 2013) - Tade, Oluwabunmi O.; Gardner, Peter; Hall, Peter S.
Abstract : Cognitive radio (CR) has generated a lot of interest because of the promise of wide instantaneous bandwidths which will improve data rates. Current social trends suggest that CR nodes will ultimately be mobile and handheld. This produces a need for small wideband antennas. The Chu limit imposes a restriction on what is obtainable with passive matching. In this paper, it is shown how a negative impedance converter (NIC) can be used to broadband match a chassis antenna beyond what is obtainable with passive matching. It is also shown how to predict and overcome the instabilities which have limited the top frequency achievable with NICs. The noise and linearity performance of the NIC matched antenna is also shown.